Public key cryptography in resource-constrained WSN - Pathan, Al-Sakib Khan; Hong, Choong Seon (Kyung Hee University, South Korea, 2008)
In this paper we present a detailed review of the works on public key cryptography (PKC) in wireless sensor networks (WSNs). In the early days of sensor networks, public key cryptography was thought to be completely unfeasible considering its computational complexity and energy requirements. By this time, several works have proved that the lightweight versions of many well-known public key algorithms can be utilized in WSN environment. With the expense of a little energy, public key based schemes could in fact be the best choice for ensuring data security in high-security demanding WSN applications. Here, we talk about the notion of public key cryptography in WSN, its applicability, challenges in its implementation, and present a detailed study of the significant works on PKC in WSN.